KIR2DL3 and the KIR ligand groups HLA‐A‐Bw4 and HLA‐C2 predict the outcome of hepatitis B virus infection. Issue 9 (5th May 2017) - Di Bona, D.; Aiello, A.; Colomba, C.; Bilancia, M.; Accardi, G.; Rubino, R.; Giannitrapani, L.; Tuttolomondo, A.; Cascio, A.; Caiaffa, M. F.; Rizzo, S.; Di Lorenzo, G.; et al.
Summary: Killer immunoglobulin‐like receptors (KIRs) regulate the activation of natural killer cells through their interaction with human leucocyte antigens (HLA). KIR and HLA loci are highly polymorphic, and certain HLA‐KIR combinations have been found to protect against viral infections. In this study, we analysed whether the KIR/HLA repertoire may influence the course of hepatitis B virus (HBV) infection. Fifty‐seven subjects with chronic hepatitis B (CHB), 44 subjects with resolved HBV infection and 60 healthy uninfected controls (HC) were genotyped for KIR and their HLA ligands. The frequency of the HLA‐A‐Bw4 ligand group was higher in CHB (58%) than subjects with resolved infection (23%) (crude OR, 4.67; P <.001) and HC (10%) (crude OR, 12.38; P <.001). Similar results were obtained for the HLA‐C2 ligand group, more frequent in CHB (84%), than subjects with resolved infection (70%) (crude OR, 2.24; P <.10) and HC (60%) (crude OR, 3.56; P <.01). Conversely, the frequency of KIR2DL3 was lower in CHB (81%) than in subjects with resolved infection (98%) (crude OR, 0.10; P <.05). These results suggest a detrimental role of HLA‐A‐Bw4 and HLA‐C2 groups, which are associated with the development of CHB, and a protective role of KIR2DL3. A stepwise variable selection procedure, based on multiple logistic regression analysis, identified these three predictive variables as the most relevant, featuring high specificity (90.9%) and positive predictive value (87.5%) for the development of CHB. Our results suggest that a combination of KIR/HLA gene/alleles is able to predict the outcome of HBV infection.